1986
DOI: 10.1254/jjp.42.1
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Action of a Non-Sulfhydryl Angiotensin Converting Enzyme Inhibitor (CV-3317) in Various Hypertensive Models

Abstract: Abstract-The antihypertensive action of N-[N-[(S)-1-ethoxycarbonyl-3-phenyl propyl]-L-alanyl]-N-(indan-2-yl)glycinehydrochloride (CV-3317), a nonsulfhydryl compound characterized as an angiotensin converting enzyme inhibitor in our previous work, was examined in hypertensive animal models.In 2-kidney, 1 clip hypertensive rats and dogs, CV-331 7 (3 and/or 10 mg/kg, p.o.) produced a sustained antihypertensive action of about 15 to 25 mmHg. Daily oral administrations of CV-3317 (1 to 10 mg/kg/day) to spontaneousl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
0

Year Published

1986
1986
1999
1999

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…It has been reported that in SHR, the level of plasma renin is normal and the levels of vascular renin and ACE are high (21,22); in 2-kidney, 1 clip hypertensive rats, the level of plasma renin, vascular renin and vascular ACE are high (23); and in 1 -kidney, 1 clip hypertensive rats, the level of vascular renin is high (24), but vascular ACE is normal (25). and captopril elicited an anti hypertensive action only in SHR and 2 kidney, 1 clip hypertensive rats with a high vascular ACE activity (12). These findings suggest that the antihypertensive effect of CV-3317 and captopril is closely related to the inhibition of vascular ACE.…”
Section: Discussionmentioning
confidence: 71%
“…It has been reported that in SHR, the level of plasma renin is normal and the levels of vascular renin and ACE are high (21,22); in 2-kidney, 1 clip hypertensive rats, the level of plasma renin, vascular renin and vascular ACE are high (23); and in 1 -kidney, 1 clip hypertensive rats, the level of vascular renin is high (24), but vascular ACE is normal (25). and captopril elicited an anti hypertensive action only in SHR and 2 kidney, 1 clip hypertensive rats with a high vascular ACE activity (12). These findings suggest that the antihypertensive effect of CV-3317 and captopril is closely related to the inhibition of vascular ACE.…”
Section: Discussionmentioning
confidence: 71%
“…In conclusion, CV-5975 is a highly potent and long acting inhibitor of ACE activity and possesses a long-lasting anti hypertensive action in animal models of hypertension (10).…”
Section: Discussionmentioning
confidence: 88%
“…1), seemed to be the most promising ACE inhibitor (9). This agent has a potent and long lasting antihypertensive activity, as noted in various models of hyper tension in laboratory animals (10). We report here the ACE inhibitory activity of CV-5975, in vitro and in vivo, as compared with the findings on enalapril and enalaprilat.…”
mentioning
confidence: 81%
“…It is reported that angiotensin converting enzyme (ACE) inhibitors are more effective than -blockers, calcium antagonists, and diuretics in reducing left ventricular mass (LVM). 5 We therefore assessed the clinical effect of delapril hydrochloride (an ACE inhibitor) 6 from the viewpoint of echocardiographically determined cardiac function and LVH, as well as the serum concentrations of procollagen type III aminoterminal peptide (PIIIP) as reflected in the production of collagen type III.…”
mentioning
confidence: 99%